2013
DOI: 10.1021/co400075z
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot, Two-Step Synthesis of Imidazo[1,2-a]benzimidazoles via A Multicomponent [4 + 1] Cycloaddition Reaction

Abstract: A one-pot, two-step synthesis of imidazo[1,2-a]benzimidazoles has been achieved by a three-component reaction of 2-aminobenzimidazoles with an aromatic aldehyde and an isocyanide. The reaction involving condensation of 2-aminobenzimidazole with an aldehyde is run under microwave activation to generate an imine intermediate under basic conditions which then undergoes [4 + 1] cycloaddition with an isocyanide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Overview of GBB catalysts that performed best in reported catalyst screenings (single hits were omitted for clarification). TiO 2 NPs (nanopowders) [170] TMSCl 7 [37,38,53,152,155,169,176] ZnO NPs [116] Montmorillonite K-10 clay 6 [19,64,65,70,121,192] Methanesulfonic acid [52] Magnesium chloride (MgCl 2 ) 5 [134,136,193,194] Zeolite HY [195] Ytterbium triflate (Yb(OTf) 3 ) 4 HCl dioxane 4 [72,73,84,117] Bromodimethylsulfonium bromide (BDMS) [69] Indium triflate (In(OTf) 3 ) 3 [108,109,122] γ-Fe 2 O 3 @SiO 2 -OSO 3 H [71] Trifluoroacetic acid (TFA) 2 [82,165] Cationic polyurethane dispersions (CPUDs) [76] Bismuth chloride (BiCl 3 ) 2 [81,91] pTsCl [77] Silica sulfuric acid 2 [126,148] Iodine [135] Lanthanum chloride (LaCl 3 •7H 2 O) 2 [92,104] (TBBDA) [83] Piperidine 2 [162,163] (PBBS)…”
Section: Catalysts In the Gbb-3crmentioning
confidence: 99%
See 1 more Smart Citation
“…Overview of GBB catalysts that performed best in reported catalyst screenings (single hits were omitted for clarification). TiO 2 NPs (nanopowders) [170] TMSCl 7 [37,38,53,152,155,169,176] ZnO NPs [116] Montmorillonite K-10 clay 6 [19,64,65,70,121,192] Methanesulfonic acid [52] Magnesium chloride (MgCl 2 ) 5 [134,136,193,194] Zeolite HY [195] Ytterbium triflate (Yb(OTf) 3 ) 4 HCl dioxane 4 [72,73,84,117] Bromodimethylsulfonium bromide (BDMS) [69] Indium triflate (In(OTf) 3 ) 3 [108,109,122] γ-Fe 2 O 3 @SiO 2 -OSO 3 H [71] Trifluoroacetic acid (TFA) 2 [82,165] Cationic polyurethane dispersions (CPUDs) [76] Bismuth chloride (BiCl 3 ) 2 [81,91] pTsCl [77] Silica sulfuric acid 2 [126,148] Iodine [135] Lanthanum chloride (LaCl 3 •7H 2 O) 2 [92,104] (TBBDA) [83] Piperidine 2 [162,163] (PBBS)…”
Section: Catalysts In the Gbb-3crmentioning
confidence: 99%
“…Later in 2013, Sun et al reported the same strategy without the post modifications and therefore these base catalyzed conditions could be applied for the standard GBB-3CR. [162,163] In the plausible mechanism, piperidine is initially involved in the formation of the Schiff base, then with the introduction of the isocyanide component, the [4+1] cycloaddition takes place, where piperidine facilitates the 1,3-H shift resulting in rearomatization, giving the GBB-3CR product as depicted in Scheme 20.…”
Section: Catalysts In the Gbb-3crmentioning
confidence: 99%
“…In the 1 H NMR spectrum, the ethylene oxy (-OCH 2 -) and aromatic proton showed multiplet signals in the ranges of d 3.87-4.25 ppm and d 7.4-8.90 ppm, respectively, while the -NH proton showed a broad singlet at d 13.36 ppm. 13 C NMR revealed the carbon of ethylene oxy (-OCH 2 -) group as well as aromatic ring as a characteristic peak in the range of d 68.18-69.23 ppm and d 110.90-162.81 ppm, respectively. Final confirmation of the compound (3e) was obtained from ESI-MS analysis, which showed an accurate molecular ion peak at m/z 595.2, whereas the elemental analysis matched well with the theoretical value for the compound.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, crown ethers are known to be useful in various applications, e.g., phase-transfer catalysis (PTC) in organic synthesis, ion-selective sensing in analytical chemistry, membrane separation processes, and fiber-optic chemical sensing, and as electroactive substances in ion-selective membrane electrodes and spectrophotometric analytical reagents, as well as exhibiting anticancer and DNA interaction activities [1,[9][10][11][12]. Benzimidazole heterocycles are well established as ''privileged scaffolds,'' being integrated into pharmaceutical agents to form enzyme inhibitors, receptor-binding drugs, and DNA intercalators [13,14]. Benzimidazole derivatives have been reported to possess noteworthy pharmacological activities such as anticancer [15], antimicrobial [16], antihypertensive [17], cytotoxic [18], anticonvulsant [19], antileukemic [20], and antifungal properties [21].…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the synthesis reaction efficiency, a cost and time effective one-pot three-component reaction strategy is proposed as it adopts step-economical transformations to introduce structural complexity by allowing multiple bond-forming events to occur in one pot. 32 Herein, for the rst time, we report a facile yet efficient one-pot two-step synthesis of 2-(5-phenylindol-3-yl) benzimidazole compounds ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%